A Critical Look at Russell’s Philosophy of Logical Atomism - Onwuegbusi, Martin Okwu (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The main aim of this paper is to critically examine Bertrand Russellâ€™s brand of Philosophy which he describes as a kind of Logical Atomism and by means of which he puts forward a kind of Metaphysics and a certain method of Analysis for developing this type of Philosophy.  Russell, thus views the whole universe as made up of many separate entities with complex properties and various relations to each other.  Russellâ€™s philosophy is an attempt to strip off the surface complexities of the world and thus arrive at the last residue in analysis which he calls the logical atoms of reality. Keywords: Atomism, Universe, Relations, Metaphysics, Analysis, Residue.